The Clash of Civilizations between Intellectual Deviation (Exaggeration) and the Repercussions of Western Terrorism - An Analytical Critical study - AbdulRahman, Said Mohammed Hilmy; Sajed, Ali Ali Jubaily; Musa, Ibrahem Mohammed Abdo (Arab Journal for Sciences and Research Publishing, 2017)
There has been a lot of talk about terrorism and exaggeration, between excessive and negligent, as those who are involved in the excess, they have been exaggerated and extremism by the abandonment, and in contrast counter-little. Because one of the parties to one side becomes alienated by the other side, so it became half-truth and half-exaggeration, and between them moderation and mediation. And we found that the greatest delegation to the society and corrupted, and left the most impact, are deviant ideas, which was canceled in the pure Islam of Islam, and these ideas would not have been more harmful if not affected by the intellectual invasion; which is the largest war of thought imposed on us, As a phenomenon? In addition, as a procedural act affecting interested parties? Moreover, why he was not described by nonMuslims. It has become clear to us that the countries that claim peace and democracy, that they represent terrorism to silence the concept of terrorism, making them cover their solution to whom they want for one reason or another, and show the fact of corruption and prejudice to Islam, so invent all the ways and means to fight it, which is only supportive of corruption, Dictatorship, and that in the first place and the last seeks to maintain their interests under any curtain, but it did not accept the curtain based on the Islamic system. As the nation must be aware of the magnitude of the danger of American hegemony globally and Iran regionally, and reveal the triangle of a conspiracy directed towards the Islamic nation, and that conspiracy is only an extension of the old conspiracies suffered by the Muslim community since the dawn of Islam, and the extent of conspiracy suffered by the people Islam as the form of terrorism on them, and the need to recognize the reality of the conflict between civilizations and aimed at ideological rivalry, and integration in this conflict only with an emphasis on the year of stampede between the conflicting parties. And that the American western gendarmes are still following the nation, and the Muslim community is still being deceived by the lies and tricks played against it, and the latest lies and I do not think the latter will be a lie (death to America), although the slogan is actually seen as a policy of loyalty and hostility, Its truth carries deceit and a style of the methods of the apostate scoundrel in our time.